Dual EMAT and PEC non-contact probe: applications to defect testing - Edwards, R.S.; Sophian, Ali; Dixon, S.; Tian, G.-Y.; Jian, X. (Elsevier, 2006)
For many non-destructive testing (NDT) applications, more information and greater reliability can be gained by using different techniques for defect detection, especially when the methods are particularly sensitive to different types of defects. However, this will often lead to a much longer and more expensive test and is not always practical due to time and cost constraints. We have previously discussed initial experiments using a new dual-probe combining electromagnetic acoustic transducers (EMATs) generating and detecting ultrasonic surface waves, and a pulsed eddy current (PEC) sensor 1. This enables more reliable detection and sizing of surface and near-surface defects, with a reduced testing time compared to using two \{NDT\} techniques separately. In this paper, we present experiments using the dual-probe on samples which are more representative of real defects, for example testing for surface defects in rails. Several aluminium calibration samples containing closely spaced and angled slots have been measured, in addition to rail samples containing manufactured and real defects. The benefits of using the dual-probe are discussed.